(untitled) (Revista Argentina de Neurocirugía, 2022)
Abstract Introduction: The endonasal endoscopic approach has evolved fast in the last 20 years. It has evolved, from a mono-nostril approach respecting the nasal structures, to a bi-nostril approach with dislocation/removal of nasal structures and carving of flaps. In the literature and scientific meetings a great controversy arose regarding what the dimension of an adequate surgical corridor should be. The most balanced response to such controversy might be the present "Guante Blanco" approach. The objective of this paper is to describe this surgical technique step by step. Materials and Methods: Pictures of dissected cadaveric specimen (five fixed with the fresh-frozen technique and five fixed with formalin) were used to identify key anatomical landmarks and design the technique. To describe the surgical aproach step by step in a real surgery, surgical videos and protocols of patients who have undergone surgery in Tucumán between January 2020 and January 2022, were included. Results: This endonasal endoscopic approach, one and half nostril, with maximum anatomical-functional nasal preservation, trans-sphenoidal, trans-sellar is described step by step with all the author tricks and pearls. Conclusion: The "Guante Blanco" approach is a simple, adequate, and fast surgical technique. This paper presented and illustrated this approched step by step in order to help skull base surgeon in training to reproduce it. Keywords: Pituitary. Adenoma. Endoscopic endonasal approach. Skull base.